Tualang honey supplementation as cognitive enhancer in patients with schizophrenia. Issue 5 (May 2020) - Yahaya, Rosliza; Zahary, Mohd Nizam; Othman, Zahiruddin; Ismail, Rusli; Nik Him, Nik Ahmad Shaiffudin; Abd Aziz, Aniza; Dahlan, Rahima; Jusoh, Azizul Fadzli
Abstract: Introduction: Schizophrenia is a chronic mental illness with clusters of symptoms, including cognitive impairment. This study aimed to explore the effect of Tualang Honey (TH) on cognitive domains, especially as it pertained to the verbal memory of schizophrenia patients. Method: This was a cross-sectional study involved 80 individuals, diagnosed with schizophrenia. The Malay Version Auditory Verbal Learning Test (MVAVLT) was used. Data were analysed using SPSS 20.0 software. Intention to treat analysis was applied. Result: A comparison of the total learning score at eight weeks between the two groups based on time effect and time-treatment interaction favoured TH group. Conclusion: This study concludes that by supplementing schizophrenia patients with 8-week of TH did improve total learning performance across domains in the immediate memory among patients with schizophrenia. Abstract : Neuroscience; Psychiatry; Biological psychiatry; Clinical psychology; Alternative medicine; Clinical research; Schizophrenia, Cognitive enhancer, Honey, AVLT.